NSCAs Performance Training Journal - Endurance (NSCAs Performance Training Journal, 2008)
Power Training for Endurance Athletes - David Sandler: Power is a critical component of most sports; however it is often overlooked by endurance athletes. In this article learn how to implement explosive drills and exercises into a comprehensive training program to help improve endurance performance.